2015
DOI: 10.1093/mnras/stv846
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of kpc-scale line emission in barred galaxies, not linked to AGN or star formation.

Abstract: We present an analysis of the optical line emission from nearby barred galaxies, and in particular look at the radial range occupied by the bar. In many cases this region is marked by what we term a 'star formation desert', with a marked deficit of HII regions in optical narrow-band Hα imaging. Here we present long-slit spectroscopy revealing that such regions do have line emission, but that it is low-level, spatially smooth and almost ubiquitous. The relative strengths of the Hα and the spectrally adjacent [N… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 25 publications
(25 reference statements)
5
34
0
Order By: Relevance
“…This study confirmed the complete suppression of SF within the SFD region in these 4 galaxies; while some low-level diffuse line emission was detected, this showed line ratios and a smooth spatial distribution that can be much more naturally explained by an old stellar population, e.g. post-AGB stars (James & Percival 2015); see also Stasińska et al (2008), Sarzi et al (2010), Yan & Blanton (2012) and Bremer et al (2013). After correcting for this weak line emission, we fitted the remaining absorption-line spectra by a model that assumed an initially constant SF rate, followed by a sharp truncation in SF activity; the one free parameter in the model was the epoch at which this truncation occurred.…”
Section: Stellar Populations In Star Formation Desert Regionssupporting
confidence: 81%
“…This study confirmed the complete suppression of SF within the SFD region in these 4 galaxies; while some low-level diffuse line emission was detected, this showed line ratios and a smooth spatial distribution that can be much more naturally explained by an old stellar population, e.g. post-AGB stars (James & Percival 2015); see also Stasińska et al (2008), Sarzi et al (2010), Yan & Blanton (2012) and Bremer et al (2013). After correcting for this weak line emission, we fitted the remaining absorption-line spectra by a model that assumed an initially constant SF rate, followed by a sharp truncation in SF activity; the one free parameter in the model was the epoch at which this truncation occurred.…”
Section: Stellar Populations In Star Formation Desert Regionssupporting
confidence: 81%
“…Long-slit spectroscopy of the bar-region showed a diffused emission which are not found to be associated with star formation. They attribute this emission to be due to post Asymptotic Giant Branch (p-AGB) stars (James & Percival 2015). These studies suggest that the observed nuclear star burst and suppression of recent star formation (∼ 10 Myr) in the bar-region is due to the effect of bar.…”
Section: Introductionmentioning
confidence: 91%
“…Thus, we suggest here a complementary technique, based on the influence of the bar on the star formation (SF) activity in its surrounding environment, rather than within the bar itself. This paper builds on the results of a recent Hα spectroscopic study of 15 nearby barred galaxies (James & Percival 2015, henceforth JP15). These galaxies had previously been identified (James, Bretherton, & Knapen 2009) as having a specific pattern of emission in continuum-subtracted narrow-band Hα imaging, with a pronounced dip in this emission in the radial range swept out by the bar.…”
Section: Introductionmentioning
confidence: 98%